Comprehensive economic evaluation of thermotherapy for the treatment of cutaneous leishmaniasis in Colombia (2018)
Background: Cutaneous leishmaniasis causes a high disease burden in Colombia, and available treatments present systemic toxicity, low patient compliance, contraindications, and high costs. Objective: To estimate the cost-effectiveness of thermotherapy versus Glucantime in patients with cutaneous leishmaniasis in Colombia. Methods: Cost-effectiveness study from an institutional perspective in 8,133 incident cases. Data on therapeutic efficacy and safety were included, calculating standard costs; the outcomes were disability adjusted life years (DALYs) and the number of patients cured. The information sources were the Colombian Public Health Surveillance System, disease burden studies, and one meta-analysis of controlled clinical trials. Incremental cost-effectiveness was determined, and uncertainty was evaluated with tornado diagrams and Monte Carlo simulations. Results: Thermotherapy would generate costs of US$ 501,621; the handling of adverse effects, US$ 29,224; and therapeutic failures, US$ 300,053. For Glucantime, these costs would be US$ 2,731,276, US$ 58,254, and US$ 406,298, respectively. With thermotherapy, the cost would be US$ 2,062 per DALY averted and US$ 69 per patient cured; with Glucantime, the cost would be US$ 4,241 per DALY averted and US$ 85 per patient cured. In Monte Carlo simulations, thermotherapy was the dominant strategy for DALYs averted in 67.9% of cases and highly cost-effective for patients cured in 72%. Conclusion: In Colombia, thermotherapy can be included as a cost-effective strategy for the management of cutaneous leishmaniasis. Its incorporation into clinical practice guidelines could represent savings of approximately US$ 10,488 per DALY averted and costs of US$ 116 per additional patient cured, compared to the use of Glucantime. These findings show the relevance of the incorporation of this treatment in our country and others with similar parasitological, clinical, and epidemiological patterns.